2020
DOI: 10.1186/s13287-020-01766-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel venom-based peptides (P13 and its derivative—M6) to maintain self-renewal of human embryonic stem cells by activating FGF and TGFβ signaling pathways

Abstract: Background: In our previous study, a venom-based peptide named Gonearrestide (also named P13) was identified and demonstrated with an effective inhibition in the proliferation of colon cancer cells. In this study, we explored if P13 and its potent mutant M6 could promote the proliferation of human embryonic stem cells and even maintain their self-renewal. Methods: The structure-function relationship analysis on P13 and its potent mutant M6 were explored from the molecular mechanism of corresponding receptor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“… 58 Ma et al reported that short peptides, P13 and M6, which support the self-renewal of hESCs, bound to the plasma membrane without penetrating into cytoplasm. 59 To examine whether WWASKS penetrates into the cytosol, we carried out a cell fractionation experiment. The FITC-peptide untreated group served as a control for the experiment.…”
Section: Resultsmentioning
confidence: 99%
“… 58 Ma et al reported that short peptides, P13 and M6, which support the self-renewal of hESCs, bound to the plasma membrane without penetrating into cytoplasm. 59 To examine whether WWASKS penetrates into the cytosol, we carried out a cell fractionation experiment. The FITC-peptide untreated group served as a control for the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have developed ECM‐derived peptide‐immobilised dishes for the proliferation of hPSCs [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Melkoumian et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have developed ECM‐derived peptide‐immobilised dishes for the proliferation of hPSCs [11–26]. Melkoumian et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of synthetic peptides as a component within engineered biomaterials is now a standard technique [ 34 , 35 , 36 , 37 ]. Recently, researchers have focused on identifying and exploring the use of peptide and peptide derivatives as potential candidates for the development of 2D or 3D cell-culture materials to tailor the stem cell’s microenvironment to further improve the adhesion, proliferation, and differentiation of stem cells [ 38 , 39 , 40 , 41 ]. For instance, peptides have been grafted to a variety of synthetic polymers to endow the material with cell-adhesive, enzymatically degradable, and growth-factor-binding properties [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%